2008
DOI: 10.1190/1.2828977
|View full text |Cite
|
Sign up to set email alerts
|

Electrodic voltages in the presence of dissolved sulfide: Implications for monitoring natural microbial activity

Abstract: There is growing interest in the development of new monitoring strategies for obtaining spatially extensive data diagnostic of microbial processes occurring in the earth. Open-circuit potentials arising from variable redox conditions in the fluid local-toelectrode surfaces ͑electrodic potentials͒ were recorded for a pair of silver-silver chloride electrodes in a column experiment, whereby a natural wetland soil containing a known community of sulfate reducers was continuously fed with a sulfate-rich nutrient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Biogeophysics is a rapidly evolving Earth science discipline concerned with the links between dynamic subsurface microbial processes, microbial‐induced alterations to geologic materials, and geophysical signatures [ Atekwana and Slater , 2009]. There is growing interest in applying electrical geophysical techniques (resistivity, complex conductivity, and self potential (SP)) for biogeophysical projects as they have repeatedly been shown to be sensitive to bacterial cells, microbial growth and microbe‐mineral alterations [ Atekwana et al , 2004a, 2004b; Naudet et al , 2004; Personna et al , 2008; Slater et al , 2008]. Previous studies have confirmed the potential of electrical geophysics for characterizing microbial production of metabolic byproducts and resulting alteration of mineral surfaces [ Werkema et al , 2003; Atekwana et al , 2004a, 2004b; Allen et al , 2007; Che‐Alota et al , 2009], evaluating hydrological and biotransformations due to microbial reduction of heavy metals [ Hubbard et al , 2008; Williams et al , 2009], improving understanding of metal and nutrient cycling driven by microbe‐mineral transformations [ Ntarlagiannis et al , 2005b; Williams et al , 2005; Personna et al , 2008], and detection of microbes, microbial growth and biofilm formation [ Abdel Aal et al , 2004; Prodan et al , 2004; Ntarlagiannis et al , 2005a; Davis et al , 2006; Abdel Aal et al , 2009; Ntarlagiannis and Ferguson , 2009; Slater et al , 2009].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Biogeophysics is a rapidly evolving Earth science discipline concerned with the links between dynamic subsurface microbial processes, microbial‐induced alterations to geologic materials, and geophysical signatures [ Atekwana and Slater , 2009]. There is growing interest in applying electrical geophysical techniques (resistivity, complex conductivity, and self potential (SP)) for biogeophysical projects as they have repeatedly been shown to be sensitive to bacterial cells, microbial growth and microbe‐mineral alterations [ Atekwana et al , 2004a, 2004b; Naudet et al , 2004; Personna et al , 2008; Slater et al , 2008]. Previous studies have confirmed the potential of electrical geophysics for characterizing microbial production of metabolic byproducts and resulting alteration of mineral surfaces [ Werkema et al , 2003; Atekwana et al , 2004a, 2004b; Allen et al , 2007; Che‐Alota et al , 2009], evaluating hydrological and biotransformations due to microbial reduction of heavy metals [ Hubbard et al , 2008; Williams et al , 2009], improving understanding of metal and nutrient cycling driven by microbe‐mineral transformations [ Ntarlagiannis et al , 2005b; Williams et al , 2005; Personna et al , 2008], and detection of microbes, microbial growth and biofilm formation [ Abdel Aal et al , 2004; Prodan et al , 2004; Ntarlagiannis et al , 2005a; Davis et al , 2006; Abdel Aal et al , 2009; Ntarlagiannis and Ferguson , 2009; Slater et al , 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that electrodic potential (EP) measurements, using simple in construction and inexpensive electrodes, can be utilized to capture temporal and spatial variability in sulfide chemistry associated with microbial sulfate reduction under anaerobic conditions [ Williams et al , 2007; Personna et al , 2008; Slater et al , 2008]. The EP measurements record the tendency for spontaneous redox reactions to occur on the surfaces of metal and/or metal‐metal salt electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under conditions where the measurement and reference electrodes are (1) located in geochemically distinct redox environments and (2) exposed to their local geochemical environment, a subset of the SP method, referred to as the electrodic potential (EP) method, has been shown to be sensitive to electrochemical reactions involving the electrodes themselves [ Corry , 1985; Nyquist and Corry , 2002; Williams et al , 2007; Slater et al , 2008]. When bridged through a measuring voltmeter, electrodes located in the electrochemically distinct regions constitute a galvanic cell, generating a voltage potential that persists as long as the concentration gradient is maintained.…”
Section: Introductionmentioning
confidence: 99%